Disentangling Timing Uncertainty of Event-Driven Connectedness among Oil-Based Energy Commodities - Evžen Kočenda; Daniel Bartušek (CESifo GmbH, 2024)
Reported news events frequently influence the pricing dynamics of oil-based commodities. We analyze almost 900 oil-related events from 1987 to 2022, categorizing them based on recurring characteristics. We quantify dynamic connectedness among energy commodities and apply a novel bootstrap-after-bootstrap testing procedure to identify 21 statistically significant historical events that triggered abrupt and enduring increases in volatility connectedness. Geopolitical events are more consistently associated with elevated connectedness than economic events, while natural events do not exhibit a similar impact. Events share prevailing characteristics: their negativity, unexpected nature, and the introduction of concerns about oil supply shortages.
Keywords: C32; C58; G15; Q02; Q35; 330; energy commodities; crude oil; volatility connectedness; systemic events; bootstrap-after-bootstrap procedure